PENGARUH MEDIA APLIKASI SITUS WEBTERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IX PADA MATA PELAJARAN IPS DI SMP N 1 PALEMBANG - Suci Wulandari; Yulia Djahir; Fitriyanti . (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2014)
Abstract: The purpose of this research is to know the difference of media application effect of website with microsoft powerpoint application to the learning result of class IX students in IPS subjects in SMP N 1 Palembang. The research is a type of Quasi Experimental Design research with nonequivalent Control Group Design. The population in this study is the students of class IX SMP N 1 Palembang odd semester of the academic year 2013/2014 consisting of 7 classes with the number of 212 students. The sample was taken by using cluster random sampling technique and got two classes that is class IX.1 as experiment class which amounted to 30 students and class IX.3 as control class which amounted to 30 students. Technique of collecting data is obtained by using learning result test and observation of learning activity. The statistics used to analyze the data in proof are parametric statistics through t-related tests (for paired samples) with a significance level of 5%, and degrees of freedom dk = n1 + n2 - 2 so (dk = 30 + 30 - 2 = 58) which means t_hitung> t_tabel = 3.14? 2.0021 then Ho is rejected and Ha accepted. The result of this research conclude that there is difference of influence of web application media with the powerpoint media toward the learning result of class IX students in social studies subject at SMP N 1 Palembang. It can be seen in the learning outcomes of IPS learners who are given media application web site is higher than the results of learning IPS learners who are given media powerpoint. Therefore, the media application of this website and media powerpoint can be used as an alternative for teachers in improving learners' learning outcomes.Abstrak :Tujuan penelitian ini adalah untuk mengetahui perbedaan pengaruh media aplikasi situs web dengan aplikasi microsoft powerpointterhadap hasil belajar peserta didik kelas IX pada mata pelajaran IPS di SMP N 1 Palembang. Penelitian yang dilakukan adalah jenis penelitian Quasi Eksperimental Design dengan bentuk nonequivalent Control Group Design. Populasi dalam penelitian ini adalah peserta didik kelas IX SMP N 1 Palembang semester ganjiltahunajaran 2013/2014 yang terdiri dari 7 kelas dengan jumlah 212 peserta didik. Sampel diambil dengan menggunakan teknik cluster random sampling dan didapatlah dua kelas yaitu kelas IX.1 sebagai kelas eksperimen yang berjumlah 30 peserta didik dan kelas IX.3 sebagaikelaskontrol yang berjumlah 30pesertadidik.Teknikpengumpulan data diperoleh menggunakanteshasilbelajardanobservasiaktivitaspembelajaran.Statistik yang digunakan untuk menganalisis data dalam pembuktian adalah statistik parametris melalui uji-t related (untuk sampel berpasangan) dengan taraf signifikansi 5%, dan derajat kebebasan dk = n1 + n2 – 2 jadi (dk = 30 + 30 - 2= 58)yang berarti = 3,14? 2,0021 makaHo ditolak dan Ha diterima. Hasil penelitian menyimpulkan bahwa ada perbedaan pengaruh media aplikasisitus web dengan media powerpoint terhadap hasil belajar peserta didik kelas IX pada mata pelajaran IPS di SMP N 1 Palembang. Hal tersebut dapat dilihat pada hasil belajar IPS peserta didik yang diberi media aplikasisitus web lebih tinggi daripada hasil belajar IPS peserta didik yang diberi media powerpoint. Oleh karena itu, media aplikasisitus web dan media powerpoint ini dapat dijadikan salah satu alternatif bagi guru dalam meningkatkan hasil belajar peserta didik.